Analisis Kesiapan Mental pada Atlet Bola Tangan Kota Surabaya Menjelang Porprov Jawa Timur 2022 - Masitha Dewi Aulia; Abdul Aziz Hakim (Indonesian Journal of Kinanthropology (IJOK), 2021)
Background: This study aims to determine the mental readiness of handball athletes in the city of Surabaya, both male and female, ahead of PORPROV VII East Java 2022 assessed according to the athlete's perception. Methods: The sample in this study were handball athletes in the city of Surabaya, a total of 28 people consisting of 14 male athletes and 14 female athletes. The instrument used in this study was to collect primary data from questionnaires distributed to Handball Athletes in the City of Surabaya via google form media, wich were then processed using qualitative descriptive methods. Results: Based on the results of this study, it can be concluded that in the self-confidence category with 5 people (18%), emotional control / behavior 5 people (18%), concentration 4 people (14%), effort / process 5 people (18%), motivation 9 people (32%). In the mental readiness of the handball athletes in the city of Surabaya, it really contributes to efforts to improve in terms of emotional/behavioral control and concentration of the handball athletes in the city of Surabaya in preparation for PORPROV VII East Java 2022. Conclusions: Based on the summary of the research results and the description of the discussion, there is a strong relationship that the mental readiness of handball athletes in the city of Surabaya ahead of PORPROV East Java 2022, which must be improved, namely in concentration and an increase in athlete motivation to improve mental performance.